Author’s genre definition as a comprehension of the new reality (based on the drama of Ukrainian emigration writers in the middle of the twentieth century) - Антонович, Світлана Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
This article is devoted to the study of author’s genre definitions as a way to grasp the new reality in which the Ukrainian emigration playwrights appeared in the middle of the twentieth century. It is found out that the originality of author’s nominations was caused by the need for a philosophical rethinking of time, definition of moral and ethical priorities. The original genre marking of plays reflects social, political, psychological changes in the life of both society and the individual, drawing attention to the actual problems of that time. The author’s definition of plays is often subjective. It points to the artist’s experience, focusing mainly on the emigration processes of the mid-twentieth century. It was proved that the practice of author subtitles, in addition to attempts to indicate a historical and cultural paradigm, indicated the complexity of the communicative ability of emigration writers in the foreign-language space. Also, genre definitions indicated the thirst for self-expression, which in the Soviet Union was impossible, and in the new conditions is an indispensable attribute of self-affirmation, a kind of evidence of the existence of each individual. The fact of creation of new genre nominations, consonant with creative searches of artists due to the thought of the crisis of the theater of the twentieth century reigning in the contemporary world cultural space, is important. The activation of the personality and author’s component in the subheadings marks of a departure from the canonical genres, which should be assumed, could not adequately realize the ideological idea of emigration artists. In this way, playwrights not only expanded the structural and semantic capacity of the genre, but also confirmed their right to interpret their own works.